PENGARUH STRUKTUR MODAL, UKURAN ERUSAHAAN DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PT. MULTIGRYA FINANSIAL PERSERO - Maryanto Maryanto; Irwan Muslim (LP2M Universitas Bina Bangsa, 2024)
PT Sarana Multigriya Financially (Persero), hereinafter referred to as SMF or the Company, cannot be separated from the history of the Indonesian nation. This history began in 1983, where the government discussed the establishment of secondary housing finance institutions among housing finance industry stakeholders. This research uses quantitative methods, namely explaining the relationship between variables, testing theories, making a picture or descriptive about a situation objectively using numbers, starting from data collection, data interpretation and appearance and results. measured by Return Of Assets (ROA) in 2011-2021 fluctuated with an average ROA value of 0.0199 or 1.99%. The DER value of PT Multigriya Keuangan Persero in 2011-2012 fluctuated with an average value of 0.556 or 55.68%. Ln Value Total assets of PT Multigriya Finansial Persero in 2011-2012 experienced an average value fluctuation of 29.44 or 2.520%. The Current Ratio (CR) of PT Multigriya Finansial Persero in 2011-2012 experienced an average value fluctuation of 29.44 or 2.520%. Based on the results of the t test, a calculated value of 0.060 was obtained with a significance level of 0.954. The amount of influence of each independent variable on the dependent variables, namely Capital Structure, Company Size, and Liquidity on the Profitability of PT. The Company's Financial Multigriya for the 2011-2021 period amounted to 64.5%. While the rest (100% - 64.5%) i.e. 35.5% was influenced by other variables that were not studied in this study